Shallow vs. Deep subsurface structures of Central Luconia Province, offshore Malaysia reveal by aeromagnetic, airborne gravity and seismic data - Jamaludin, S.N.F. (MDPI AG, 2021)
Across the Luconia continental shelf, the nature and structures of the crust are lacking geological understanding and precise characterization. Newly acquired, aeromagnetic, and airborne gravity data were used to assess deep and shallow sub-surface signals within the Central Luconia Province, off the coast of Sarawak, offshore Malaysia. Regional aeromagnetic anomalies appear to primarily reflect deep crustal features while depth (Z) tensors of airborne gravity anomalies evidence shallow subsurface structures. Strike directions of the interpreted structural trend on aeromagnetic and airborne gravity anomalies maps are measured and plotted into rose diagrams to distinguish the structural orientations for all datasets. Signature patterns extracted from the depth profiles were correlated with parallel seismic lines and nearest exploration wells and coincide well with the top of carbonate for Cycle IV/V and structures seen within the Cycle I and II sediments. The orientation of faults/lineaments at shallower depth is dominated by a NW-SE orientation, similar with the faults extracted from two recently published structural maps. Deeper subsurface sections yielded E-W to NWW-SEE dominant directions which were never presented in the published literature. The E-W oriented anomalies are postulated to represent the remnants of the accretion between the Luconia crustal block and southern boundary of the Palawan block. The NW-SE trend follows the same direction as prominent faults in the region. The insight into shallow and deep subsurface structures in Central Luconia Province imaged through airborne gravity and aeromagnetic data should provide guidelines and complementary information for regional structural studies for this area, particularly in combination with detailed seismic interpretation. Further evaluation on the response of Air-FTGÂ® gravity and aeromagnetic could lead to the zonation of potential basement highs and hydrocarbon prospects in this area. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.